The design and Implementation of Sports Dance Teaching System Based on Digital Media Technology - Liu, Guiyou (Proceedings of the The 1st EAI International Conference on Multimedia Technology and Enhanced Learning, 2016)
In this paper, the application of virtual reality simulation technology of sports dance rehearsals were preliminary research and implementation of a virtual simulation system of sports dance rehearsal and rehearsal, the system can for the coordination of the sports dance creating staff on formation of the arrangement, the movements of the mechanical rationality and sound dance provide technical parameters, can be used as a powerful auxiliary tool for composing personnel of sports dance. The main research contents of this paper include: first to based on the physical simulation research 111e status has made the review and the summary, in order to carry out computer simulation of sports dance performance. This paper is divided into three blocks of dance in the process can not be avoided in the virtual human animation technology, dancers and edit dance of harmony harmony is discussed. At last, the three pieces of work are integrated into the final system of sports dance choreography. In the virtual human animation technology, the traditional way for the teacher to carry out a frame by frame manual labeling, heavy workload, high cost of motion capture, manual identification accuracy. In this paper, we use a combination of linear interpolation and quaternion interpolation method to capture the motion information of interpolation, to solve the problem of hopping between some separate interpolation algorithm for every frame of the animation, so that eventually the synthesis of human animation is natural, smooth and realistic. Initial animation still has a lot of problems, in order to allow the computer to make action of modified return to action subject, this paper of each rigid body motion clips do accurate and detailed data analysis, use based on keyframe the spline interpolation algorithm to solve location bias, the quaternion in value algorithm to solve the action subject or body movements rotation problem, let the computer auxiliary action scheduling system make actions to modify the fully return to virtual human animation.